Development of Pop-Up Book ‘Ayo Siaga Bencana’ to Cultivate Disaster Mitigation Awareness in Early Childhood - Khoirunnisa, Dyah; Lilis Suryani; Irma Yuliantina (JURNAL PENA PAUD, 2025)
This study aims to develop the Pop Up Book media "Ayo Siaga Bencana" (Let's Be Prepared for Disaster) to foster disaster mitigation awareness in early childhood. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation), but this study is limited to the limited scale implementation stage. The research approach uses mixed methods with children aged 5-6 years old group B at the Kembangan District PAUD institution. Needs analysis was conducted through observation, interviews, and teacher and parent questionnaires. The Pop Up Book product was validated by three experts (material, media, and practitioners) with very high feasibility percentage results, respectively 87.5% (material experts), 95% (media experts), and 87.5% (practitioner experts). The trial was carried out in stages (individual, small group, large group) in three PAUD institutions, then a limited scale implementation was carried out on 10 children in group B of Al-Ikhlas Joglo PAUD. The results showed a teacher response of 97.5% (very good category) and a child response of 95% (very good category). Thus, this Pop-Up Book is deemed suitable, engaging, and effective as a disaster mitigation learning medium for early childhood. This medium can increase children's attention, enthusiasm, and understanding of simple disaster management steps, making it an innovative alternative for preparedness education in early childhood education (PAUD).